Who's the "Real" Victim? How Victim Framing Shapes Attitudes Toward Sexual Assault. (April 2022) - Flusberg, Stephen J.; van der Vord, James; Husney, Sarah Q.; Holmes, Kevin J.
People accused of sexual assault are often described as the "real" victim by their defenders, but the impact of "victim framing" on public opinion is unknown. We investigated this issue across four experiments ( N = 2, 614). Online U.S. adult participants read a report about an alleged sexual assault that framed the female accuser as the victim (of assault), framed the male alleged perpetrator as the victim (of false accusations), or was neutral about victimhood (baseline). Relative to those in the baseline condition, participants in the assault- and allegation-victim conditions generally expressed more support for the victim-framed protagonist and less support for the other protagonist. The consistency of these effects varied with how often the victim frame was instantiated and whether the report described a fictionalized or real-world case. Across all contexts, however, participants who identified the victim-related language as influencing their evaluations exhibited strong framing effects. This suggests that social-pragmatic reasoning is a key mechanism by which victim framing shapes moral judgments.